Characteristics and agronomic performance in Paraná State of wheat cultivar BRS 220 - Bassoi, Manoel Carlos; Brunetta, Dionisio; Dotto, Sergio Roberto; Scheeren, Pedro Luiz (Pesquisa Agropecuaria Brasileira, 2005)
The cultivar BRS 220, recommended for all wheat growing regions in the Paraná State, has shown a high yield potential, wide adaptation and resistance to the main diseases, presenting a gluten suitable for baking. The cultivar belongs to medium maturity group and presents medium height, high resistance to lodging, moderate tolerance to toxic aluminium, moderate tolerance to natural dehiscence but it is susceptible to preharvest sprouting (PHS). In the experimentation over five years, BRS 220 presented a grain yield average of 4,853 kg ha-1 in the region 6, 3,794 kg ha-1 in the region 7 and 4,039 kg ha-1 in the region 8, surpassing 5%, 13% and 8% the average of the local cultivars, respectively.